KALA DALAM BAHASA WOTU (Tense in Wotu Language) - Jusmianti Garing (SAWERIGADING, 2014)
This research aims to convey tenses in Wotu language.This research applies the qualitative method to find the complete and valid data. The data is collected by library study of reading varies literature, for instance; books, journals, and other resources related to this research, in particular, theories and researches of tenses. There are eleven oral discourses of Wotu language consisting of legend, fable, sage, myth, fairy tale and Wotu sentences become the object analysis in this study. The result shows that there are no grammatical features in marking tenses of Wotu language. Tense is only marked by adverbial times that refer to absolute and relative times. The absolute times are expressed by ijiawi (yesterday), yani eyyoe (today),and laile (tomorrow). Then, relative times are expressed by idiulu (past), innie/mokokkoni (now), nono (later), laipuwa (day after tomorrow), etc.